Home » Evaluate (frac{xy^2 – x^2y}{x^2 – xy^1}) When x = -2 and y = 3

Evaluate (frac{xy^2 – x^2y}{x^2 – xy^1}) When x = -2 and y = 3

Evaluate (frac{xy^2 – x^2y}{x^2 – xy^1}) When x = -2 and y = 3

  • A.
    3
  • B.
    -(frac{3}{5})
  • C.
    (frac{3}{5})
  • D.
    -3
Correct Answer: Option D
Explanation

(frac{xy^2 – x^2y}{x^2 – xy^1})
= (frac{(-2)(3)^2 – (-2)^2(3)}{(-2)^2 – (-2)(3)})
= (frac{-30}{10})
= -3

Related:  Given that the logarithm of a number is (bar{1}.8732), find, correct to 2 significant figures...